1981
DOI: 10.3171/jns.1981.55.6.0938
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in intracranial disease: perhaps not the syndrome of inappropriate secretion of antidiuretic hormone (SIADH)

Abstract: Patients with intracranial disorders are prone to develop hyponatremia with inability to prevent the loss of sodium in their urine. This was originally referred to as "cerebral salt wasting," but more recently is thought to be secondary to the syndrome of inappropriate secretion of antidiuretic hormone (SIADH). Blood volume determinations were made in 12 unselected neurosurgical patients with intracranial disease who fulfilled the laboratory criteria for SIADH. Ten of the 12 patients had significant decreases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
124
1
12

Year Published

1983
1983
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 259 publications
(141 citation statements)
references
References 21 publications
4
124
1
12
Order By: Relevance
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…the incidence of csWs among all the patients was greater than that of sIADH, which is in agreement with reports from various other authors, who also observed a greater prevalence of csWs, compared to sIADH in neurological patients 1,2,4,5,10,18,30 . the coexistence of DI and csWs (mixed syndrome) observed in our patients has also been described by yamaki et al 17 , who studied two patients postoperatively following surgery for pituitary tumor and observed the presence of severe natriuresis and hyponatremia in a study patient who developed DI (fluid loss >2.36 ml/kg/h), which led the authors to conclude that hyponatremia resulting from csWs in intracranial diseases may develop in patients with DI.…”
Section: Discussionsupporting
confidence: 82%
“…Improved knowledge with respect to the physiology of arginine vasopressin (AVP), the possibility of its measuring by radioimmunoassay 2,[16][17][18][19][20][21] and the report of hypovolemia in the majority of neurological patients presenting hyponatremia and natriuresis, led investigators to question sIADH in brain disease. Many questions remain unanswered with respect to sIADH since few studies in which AVP was measured have been reported and results have been contradictory 1,2,7 . At the present time, csWs has again been proposed as a cause of hyponatremia associated with neurological disease.…”
mentioning
confidence: 99%
See 3 more Smart Citations